STRATEGI KEBERLANJUTAN INOVASI PERKOTAAN: STUDI KASUS PENGEMBANGAN “LORONG WISATA SYDNEY” DI KOTA MAKASSAR - Majid, Ramlan; Salman, Ade Reyhan (ADMIT: Jurnal Administrasi Terapan, 2024)
The Makassar City Government prioritizes intervention in certain Lorong Wisata (Longwis) locations based on their potential and condition. This can be seen from many Longwis locations that have not been touched by interventions, such as Longwis “Sydney” in Tello Baru Village, Panakkukang District. This Longwis was chosen because it has advantages or uniqueness that make it worth developing. This study aims to examine in depth the sustainability strategy of Longwis Sydney in empowering the local urban community. Longwis Sydney's innovation is considered successful in maintaining its program sustainably by utilizing the potential and existence of its potential ecological space. This research is urgent because it offers strategy modeling in one community to be replicated and applied in other communities. This research uses a descriptive qualitative research method with a case study approach. The results showed that Longwis Sydney places the community as the main actor through community empowerment in various tourism activities by utilizing the potential of MSMEs, green plants, fish farming, culinary and a fairly active waste bank. In maintaining the sustainability of the tourism aisle, Longwis Sydney took several approaches, including developing local economic potential through community-based tourism, utilizing high community participation and conducting effective institutional evaluations.